Phonemic awareness - Fitzpatrick, Jo; Yuh, Catherine (California : Creative Teaching Press, 1997)
This book provides engaging and easy-to-use activities that help children develop phonemic awareness, a foundational skill for reading success. It focuses on identifying, segmenting, blending, and manipulating sounds in words through rhymes, chants, games, and hands-on exercises. The book is designed for teachers working with early learners or students who need additional phonics support.
Keywords: Phonics -- Reading Skills -- Phonemic Awareness